A Report on Haremeyn (Mecca, Medina), Damascus, Jeddah, Ethiopia, Yemen, India and Egypt - (:unkn) unknown (ISTANBUL 29 MAYIS UNIV & ISAM, 2014)
Report (takrir) that we have discussed here and assumed that it was written at the end of 1525 and at the beginning of 1526 is one of the important sources about the first quarter of the XVI. century. It isn't certainly known who has written the report. The report includes important information about condition of Mecca, Medina, Damascus, Zabid, Yemen, Ethiopia, Jeddah, Egypt, India, Gujarat and about Portugal's invasion of India. In our study we discussed the writer of this source who hasn't attracted attention hitherto, when it was written and what kind of information it includes about the said areas.
Keywords: Mecca; Medina; Damascus; Zabid; Yemen; Ethiopia; Jeddah; India; Gujarat; Egypt; Portugal; report (takrir)